Современнaя политикa Кaзaхстaнa нa Корейском полуострове (Вестник КазНУ. Серия Востоковедения, 2018)
The article deals with the political aspects of international relationsbetween Kazakhstan and the Republic of Korea.Thenew trends in politicalcooperation of Astana and Seoul at the present stagewere analyzed.Authordeveloped a political approach in the relations between the two countries.The long-term prospects and the dynamics of the political cooperationbetween the two countries was disclosed.